UPAYA MENINGKATKAN KEAKTIFAN SISWA PADA PEMBELAJARAN ONLINE PAI MELALUI METODE TANYA JAWAB PADA SISWA KELAS VIII3 DI SMP NEGERI I UJUNG PADANG TAHUN PELAJARAN 2020/2021 - Rusmaini Susanti (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2021)
This research is a Classroom Action Research (CAR) which aims to increase student activity by applying the question and answer method in PAI online learning for class VIII3 SMPN 1 Ujung Padang in 2020/2021. The results showed that student activity had increased, in cycle 1, meeting 1, the score of student activity was 15.38%, at meeting 2 it was 22.11%, at meeting 3 it was scored 28.85%. In cycle 2, meeting 2, the score of student activity was 36.59%, at meeting 2 it was 41.34%, and at meeting 3 it was 77.88%. Based on these results, it can be concluded that the question and answer method can improve Indonesian language learning achievement. The conclusions in this study are, among others, (1) the use of the question and answer method can increase student activity in class VIII3 (2) The effect of the question and answer method for students in class VIII3 more active in learning, many of them ask questions or express opinions, (3) With the application of the question and answer method, Class VIII3 students can actively participate in online learning and think more critically than before, so that the class feels more alive, students give a lot of positive and positive responses. enthusiasm in online KBM, Provide experience and input for teachers and students.